Demonstrasi Dan Edukasi Latihan Untuk Optimalisasi Kondisi Physical Wellness Pada Komunitas Osteoarthritis Genue Di Wilayah Puskesmas Banyuanyar Surakarta - Innie Kurniawati; Farid Rahman; Seliana Sinta Debi (Universitas Kristen Indonesia Toraja, 2023)
Banyuanyar is a village in Banjarsari district, Surakarta. This district has Puskesmas as its role in public health of the first level with two buildings namely Banyuanyar and Source. The second-largest visit data available at Puskesmas Banyuanyar Physiotherapy Poli in 2023 was obtained from 104 patients and 11 patients in the last 1 month, which is knee osteoarthritis characterized by pain, stiffness in the knee joints so impaired day-to-day activity. The aim of this program is to help provide education and treatment as well as training in the case of knee osteoarthritis in order to reduce and prevent complaints felt worse. The method used for educational purposes is dissemination as well as providing leaflets to the Lansia Post Community at RW 14 Kelurahan Source City of Surakarta. To see the improvement in understanding, the authors using pre-test and post-test questionnaires obtained results that are significant improvements in the understanding of the physical therapy material with an average pre test score of 4,55 and an average post test rating of 95.45.